Avaliação do efeito citoprotetor do composto homeopático canova® em linhagem celular de rim de macaco verde africano (VERO) exposta ao fármaco dipirona sódica - BONFIM, Laís Teixeira (Universidade Federal do Pará, 2018)
Paracetamol, sodium dipyrone and ibuprofen are among the main medicines exempt from medical prescription available in pharmacies in Brazil. Sodium dipyrone is highlighted in the literature as one of the most commonly used drugs. Despite its wide use, our research group demonstrated that sodium dipyrone exerts genotoxic and cytotoxic effects. Therefore, studies with medicines that may provide protection or that ameliorate the possible damages caused by sodium dipyrone are very important. The homeopathic compound Canova® (CA) seems to be a good candidate for such purpose, since in combination with other drugs it seems to soften the side effects of such drugs. Therefore, the present work aims to evaluate the possible cytoprotective effect of CA on African green monkey kidney cell line (VERO) exposed to the drug sodium dipyrone using the comet, micronucleus, apoptosis and immunocytochemistry assays. Results obtained by the comet test showed that sodium dipyrone induces an increase in DNA damage index of the VERO line. However, when such cells were co-treated with CA at the three concentrations studied, a significant reduction in the ID was observed, indicating a possible antigenotoxic effect of CA. We observed in the apoptosis and necrosis assays that dipyrone induced an increase in the percentage of apoptosis in both 24 hours and 48 hours. However when the drug was associated with CA, a significant reduction in this effect was observed in the three concentrations of CA + dipyrone. Results on immunocytochemistry showed an increase in the expression of caspase 8 and cytochrome C when cells were exposed to dipyrone. On the other hand, co-treatment significantly reduced such effect. Expression of caspase 9 was also observed after dipyrone tratament, however, co-treatment did not reduce such effect. Therefore, in our experimental conditions CA acted as a cytoprotect agent against the damages induced by dipyrone.